The Diagnostic Utility of Cell Block Preparation with Conventional Cytological Smears: A Cross Sectional Study - Goswami, Falguni J; Srilakshmi, H P; Gidwani, Roopam K; Patel, Ragini; Shah, Nirali V; Shringarpure, Kalpita (Annals of Pathology and Laboratory Medicine, 2019)
Background: Cytological examination of serous fluids aspirated is a simple and relatively non-invasive technique to diagnose whether the effusion is malignant or benign. Cell block preparation along with conventional smear increases the sensitivity of detecting malignancies, and also has the ability to reduce false-positive interpretations. Methods: A total 68 samples of body fluid (pleural and ascitic) specimens were examined for conventional cytological smear (CS) and cell block method (CB) over a period of one year. Out of 68 fluids, 40 were pleural fluid and 28 were ascitic fluid. Each fluid specimen was examined by conventional smear technique as well as cell block technique. The morphological details, cellularity, architecture, nuclear and cytoplasmic details were studied in both CS and CB techniques. Result: A total 82.35% smears had adequate material; while of the total cell blocks, 75% cell blocks had adequate material. A total of 11.76% cases were malignant on smears,5.88% were suspicious of malignancy, 64.7% were benign/non-neoplastic lesions. A total 13.2% cases were malignant on cell block, 1.47% were suspicious of malignancy, 60.29% were benign/non-neoplastic lesions. Sensitivity, positive and negative predictive value and accuracy of cell block technique were greater than that of FNAC smears Conclusion: For the final cytodiagnosis of body fluid, there is statistically significant difference between the two techniques. Cell blocks prepared from the residual fluid specimen can be useful for more definitive diagnosis, with advantage of IHC and special stains where required.